How to stop time - Haig, Matt, 1975- (Canongate, 2017)
Tom Hazard has been alive for centuries because of a rare condition. He moves back to London to become a high school history teacher--the perfect job for someone who has witnessed the city's history first hand. Better yet, a captivating French teacher at his school seems fascinated by him. But the Albatross Society, the secretive group which protects people like Tom, has one rule: Never fall in love.